Comparison of the gut microbiota in the groundwater amphipod Crangonyx islandicus Svavarsson & Kristjánsson, 2006 (Amphipoda: Crangonyctidae) to biofilms in its spring-source habitat - Gudmundsdóttir, Ragnhildur; Björnsdóttir, Snædís H; Marteinsson, Viggó Þ; Pálsson, Snæbjörn (Journal of Crustacean Biology, 2020)
Abstract Crangonyx islandicus Svavarsson & Kristjánsson, 2006 is a groundwater amphipod endemic to Iceland and restricted to spring sources at edges of lava fields in the volcanically active zone. Genetic analysis indicate that the amphipod has survived in subglacial refugia in the groundwater in Iceland during past Ice Ages. We investigated the gut bacteria of C. islandicus and compared them with the bacterial diversity identified in biofilms from its groundwater habitat. The diversity of both uncultivated and cultivated bacteria was analyzed using partial 16S rRNA gene sequences. The results show that iron-oxidizing bacteria such as Sideroxydans and Gallionella and the methanotroph Methylobacter are common in the biofilm but absent from the gut samples. Thiomonas was common in both the biofilm and the gut samples. The cultivation of gut bacteria revealed that most of the taxa could be linked with terrestrial soil and/or freshwater habitat based on available database entries. This indicates that the food source for the amphipods is partly of terrestrial origin. The presence of primary producers in the subsurface habitat of C. islandicus indicate that microbial chemolithotrophic activity might fuel the system at least partly and thus explain the amphipod survival in the subsurface of Iceland during repeated glaciation for the past 5 mya.